Factors for a socially acceptable gene technology - Latifah Amin; Abd Rahim Md Nor; Jamaluddin Md. Jahi; Mohamad Osman; Nor Muhammad Mahadi (Environmental Management Society, Malaysia, 2005)
Public perceptions of biotechnology have received extensive attention in recent years in most Western countries such as Europe, USA and Canada but there have been limited similar surveys in developing countries. Most of the earlier studies used uni-dimensional or bi-dimensional instrument with multi-items or the most is four dimensions with single item. In this study, public attitude towards genetically modified food was based on multi-dimensions and multi-items instrument. Respondents were asked their attitude on genetically modified soybean that is already available in the Malaysian market. A survey was carried out on 440 respondents from various expert groups in the Klang Valley region. In order to detect the structure of attitude amongst the expert group in the Klang Valley region, structural equation modelling (SEM) using AMOS version 5.1 was carried out. Result of the survey has confirmed that attitude towards complex issues such as biotechnology should be seen as a multi-faceted/multidimensional process. The most important factors predicting encouragement of GM soybean are the specific application-linked perceptions about the benefits, acceptance of risk and moral concern while risk and familiarity are significant predictors of benefit and risk acceptance. Researchers, policy makers and industries interested in developing and marketing GM products in Malaysia should consider the various factors mentioned in this study in order to gain public approval